On anxiety – a few thoughts - Biegalska, Agnieszka (Filozofia Chrześcijańska, 2016)
The article constitutes a voice in the interdisciplinary discussion on anxiety. The phenomenon of anxiety is illustrated through three research fields: medical (psychiatric) discourse, theological discourse and philosophical discourse. The ambition of the author is to outline how philosophy serves to complement the research problem, referring to sources of anxiety in the modern man as well as possible ways out of the situations dominated by anxiety.